Gender roles, generational changes and environmental challenges: an intersectional interpretation of perceptions on healthy diets among iTaukei women and men in Fiji. Issue 11 (9th November 2022) - McKenzie, Briar Louise; Waqa, Gade; Hart, Ashleigh Chanel; Moala Silatolu, Anasaini; Palagyi, Anna; Norton, Robyn; McLean, Rachael; Webster, Jacqui
Abstract: Objective: To investigate perceptions of iTaukei Fijian women and men around diet and the ability to consume a healthy diet. Design: Six focus groups were conducted with women and men separately. Six to ten women and men participated in each group. Discussions were recorded, transcribed, translated and thematically analysed. Themes were mapped to an intersectionality framework to aid interpretation. Setting: Four villages in Viti Levu, Fiji. Participants: Twenty-two women and twenty-four men. Results: Seven overarching themes were identified, including generational changes in food behaviour, strong-gendered beliefs around food and food provision, cultural and religious obligations around food, the impact of environmental change on the ability to consume a healthy diet, perceptions of the importance of food, food preferences and knowledge. Participants across focus groups identified that it was the 'duty' of women to prepare food for their families. However, some women reflected on this responsibility being unbalanced with many women now in the formal workforce. Changes between generations in food preferences and practices were highlighted, with a perception that previous generations were healthier. Power dynamics and external factors, such as environmental changes, were identified by women and men as crucial influences on their ability to eat a healthy diet. Conclusion: Embedded traditional perceptions of gendered roles related to nutrition were misaligned with other societal and environmental changes. Given factors other than gender, such as broader power dynamics and environmental factors were identified as influencing diet, viewing nutrition-related issues through an intersectional lens is important to inform equitable food policy in Fiji.